Influence of the Housing Development Type on the Living Environment Comfort - Lipyanin, Vadim; Milash, Tetiana; Pilipaka, Liudmyla; Yurin, Oleg (International Journal of Engineering and Technology, 2018)
The article is devoted to the problems of rational use of urban areas, namely: the optimal planning of its residential development. Microdistrict and block housing development sites in the cities of Europe and Ukraine were researched. A city-planning assessment of population density and building density was carried out using a comparative analysis of microdistrict and block type of housing development of residential complexes and influence of the planning structure on the population living comfort was determined. The article presents the justification of the fact, that effective mass housing development is medium-floor block, with a convenient network of streets, designed primarily for pedestrians, dense, which in turn will significantly improve the comfort of the living environment in the cities of Ukraine.Â Â